2003
DOI: 10.1128/aem.69.3.1337-1346.2003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Populations Stimulated for Hexavalent Uranium Reduction in Uranium Mine Sediment

Abstract: Uranium-contaminated sediment and water collected from an inactive uranium mine were incubated anaerobically with organic substrates. Stimulated microbial populations removed U almost entirely from solution within 1 month. X-ray absorption near-edge structure analysis showed that U(VI) was reduced to U(IV) during the incubation. Observations by transmission electron microscopy, selected area diffraction pattern analysis, and energy-dispersive X-ray spectroscopic analysis showed two distinct types of prokaryoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(114 citation statements)
references
References 45 publications
4
109
0
1
Order By: Relevance
“…Other field studies observed bacterial population shifts during short-term push-pull stimulations, which were predominated by iron-reducing populations (North et al, 2004) or a mix of sulfate-reducing and/or iron-reducing populations (Abdelouas et al, 2000;Vrionis et al, 2005), whereas others observed predominance by sulfate reducing bacteria (SRBs), namely Desulfosporosinus (Nevin et al, 2003), Desulfosporosinus and Clostridium (Suzuki et al, 2003), Desulfobacter species (Vrionis et al, 2005). Over the tested period in our study, the communities became dominated by sulfate-reducing populations closely related to Desulfovibrio species.…”
Section: Engineering Controlsmentioning
confidence: 63%
“…Other field studies observed bacterial population shifts during short-term push-pull stimulations, which were predominated by iron-reducing populations (North et al, 2004) or a mix of sulfate-reducing and/or iron-reducing populations (Abdelouas et al, 2000;Vrionis et al, 2005), whereas others observed predominance by sulfate reducing bacteria (SRBs), namely Desulfosporosinus (Nevin et al, 2003), Desulfosporosinus and Clostridium (Suzuki et al, 2003), Desulfobacter species (Vrionis et al, 2005). Over the tested period in our study, the communities became dominated by sulfate-reducing populations closely related to Desulfovibrio species.…”
Section: Engineering Controlsmentioning
confidence: 63%
“…Environmental microbial community analyses have shown that Gram-positive bacteria are represented in several U(VI)-contaminated sites, suggesting the potential relevance of these strains in the remediation process (Chang et al, 2001;Suzuki et al, 2002, N'Guessan et al, 2008, Dong et al, 2006. Therefore, recent research has focused on the characterization of U(VI) reduction by Clostridium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, U contaminated settings such as mine sites, mill tailings, and sites where nuclear weapons have been manufactured have been studied directly by field observations or indirectly in laboratory experiments in which sediment and water samples collected from the field have been used to simulate in situ biogeochemical processes. The laboratory amendment of field sediments with organic substrates as electron donors to stimulate anaerobic microbial respiration typically results in significant removal of U from the pore water within a short period (< 1 month) (Abdelouas et al, 1999;Abdelouas et al, 2000;Finneran et al, 2002a;Finneran et al, 2002b;Suzuki et al, 2002;Elias et al, 2003a;Nevin et al, 2003;Suzuki et al, 2003;North et al, 2004;Gu et al, 2005a;Senko et al, 2005b;Tokunaga et al, 2005;Wan et al, 2005). No U(VI) reduction has been observed in the abiological controls, which strongly suggests that U(VI) reduction is biologically mediated.…”
Section: Redox Transformations Of U In U-contaminated Settingsmentioning
confidence: 88%
“…Under sulfate rich conditions, sulfate reducing Desulfosporosinus spp. appear to be associated with the stimulated U(VI) reduction (Nevin et al, 2003;Suzuki et al, 2003). In slightly acidic sediments, Anaeromycobacter spp.…”
Section: Redox Transformations Of U In U-contaminated Settingsmentioning
confidence: 99%
See 1 more Smart Citation